Knowledge, attitudes and practices regarding telerehabilitation among Tunisian physical therapists - Ghassen Kharroubi; Emna Arfaoui; Ines Cherif; Rabeb Gharbi; Walid Affes; Jihene Bettaieb (BMC Health Services Research)
Abstract Background The COVID-19 pandemic forced the physical therapists to explore digital physical therapy as an alternative approach to delivering healthcare services, ensuring uninterrupted patient care. This study aimed to investigate the knowledge, attitudes and practices of Tunisian physical therapists regarding telerehabilitation (TR). Methods A cross-sectional study was conducted during March 2023, among a simple random sample of physical therapists practicing in the private sector in Greater Tunis. Data related to knowledge, attitudes and practices of participants regarding TR were collected using a standardized questionnaire. A multivariable analysis by logistic regression was performed to assess the factors associated with intention to practice TR. Results In total, we included 200 physical therapists with a median age of 32 years (interquartile range: [29–36]), and a sex-ratio (M/F) equal to 0.16. More than half of the participants (59%) were aware about TR, among them 49.2% had already used this approach. The prevalence of previous TR practice among all participants was 29% (95% CI: 23.0-35.5). The main reported obstacles bounding the use of TR were the lack of physical contact (56.9%), physical therapist-patient communication problems (22.4%) and technical complexity (15.5%). More than half of physical therapists (57%) expressed an intention to practice TR in the future. In multivariable analysis, higher intention to practice TR was found among participants under 35 years (Adjusted OR (AOR) = 2.23 [1.10–4.52]), those who were familiar with communication technologies (AOR = 6.68 [1.94–22.98]), those who received encouragement to practice TR (AOR = 4.73 [1.38–16.21]), and those who previously used TR (AOR = 8.96 [3.26–24.66]). Conclusions In our study, we observed a low prevalence of TR practice. It is advisable to implement specialized training programs at both at undergraduate and post graduate levels to equip physical therapists with the necessary skills for this approach. Additionally, improving digital literacy among physical therapists and promoting TR will support the adoption of this approach.